Establishing an Effective Blended Learning Model: Teacher Perceptions from the United Arab Emirates - Wasif Minhas (SAGE Publishing, 2021)
Blended learning is fast becoming the new normal and increasingly considered an integral part of program offers within higher education (HE) institutions. Although there is a general consensus about online and physical face to face components, which constitute a framework for blended learning models. There are variances on how these components should be combined, established, and delivered. Empirical evidence on teachers’ perceptions of these elements is also limited. This qualitative study used focus groups to gather teacher perspectives of blended learning models, which produced three major themes related to professional development, student success, and blended courses. A sample of teacher from this group was most relevant to the study because they were involved in the implementation, and iterations, of blended learning at their HE institution for three semesters. Their experiences and perceptions provided highly relevant insights on what constitutes an effective blended leaning model. This study confirms previous empirical claims on the importance of professional development in increasing teacher efficacy. But also reveals the role of self-learning, informal communities of practice and their impact on changing teacher perceptions, which in turn improve efficacy. The study also highlights effective communication, course materials, course design and how blended learning environments are set-up, as crucial elements of an effective blended learning model. Teachers perceived these elements as the biggest influences on student success. This study provides important insights for educational institutions seeking to establish or improve their blended learning strategy and enhance student experience.